Stethoscopes with hearing aid use: Case studies - Jacob, Regina Tangerino de Souza; Zambonato, Ticiana Cristina de Souza; Mondelli, Maria Fernanda Capoani Garcia (International Archives of Otorhinolaryngology, 2013)
Introduction: Description for using stethoscopes adapted to hearing aids.Aim: To describe the adaptation of HAs to stethoscopes used by 2 students in the health field with bilateral hearing impairment. Case reports: Two subjects with hearing loss had their stethoscopes coupled to HAs because of the individual requirements of their professions (healthcare) to perform auscultation. Conclusion: The improvement was measured in situ, and satisfaction was evaluated using a subjective questionnaire. The use of a stethoscope coupled to an HA allowed students with hearing loss to perform auscultation.
Keywords: Stethoscopes; Hearing Aids; Hearing Loss